Just say goodbye - Walting, Matt; O'Shea, Layla; Eichenberger, Katerina; Mackenzie, Max, 1997-; Galatis, William, 1979-; Walting Entertainment (Firm); Leomark Studios ([Wilbraham, Massachusetts] : Walting Entertainment, 2017)
After enduring years of abuse from his alcoholic father and the school bully Chase, Jesse Peterson tells his best friend Sarah that he plans on committing suicide. After promising to tell no one, Sarah finds it upon herself to try to stop him, taking any means necessary. --
Originally released as a motion picture in 2017.
Katerina Eichenberger, Max Mackenzie, William Galatis, Jesse Walters, Pamela Jayne Morgan, Charlotte Cusmano Zanolli.
Cinematographer, Jeff Simons ; editor, Matt Walting ; original scores by Diana Jeffery, Joshua Kaster.
In English; closed captioning available.
Winner of the Award of Best Director, at the Boston International Film Festival 2018
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2021)
Keywords: Teenagers -- Suicidal behavior -- Drama; Friendship -- Drama; Suicide -- Drama; Feature films; Fiction films; Internet videos; Streaming video